"Please Pollinate!". Issue 2 (September 2015) - Klein, Alexandra‐Maria
Abstract Wild bees find it hard to survive in intensively managed agricultural landscapes, and when the number of pollinating insects diminishes, it isn't just crop yields that are affected. As ecologists have demonstrated in Californian almond plantations, the type of pollination can even affect the quality of the fruits.